2017
DOI: 10.1111/trf.14067
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in necrotizing soft tissue infections treated with therapeutic plasma exchange

Abstract: This study describes the largest series of patients with NSTIs treated with TPE and showed no evidence of clinical benefit. Further carefully designed studies with meaningful clinical endpoints would prove useful in assessing reproducibility and determining if there is a role for TPE in other forms of severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…In addition, poor vascularization and antibiotic degradation limit antibiotic delivery to the fascial tissue (Montrief et al, 2019). In the face of these obstacles, it has been suggested that therapeutic plasma exchange can improve organ function and reduce mortality by decreasing circulating inflammatory mediators in the blood (Saifee et al, 2017). Unfortunately, this method is still not recommended as adjuvant therapy in the treatment of necrotizing soft tissue infections (Saifee et al, 2017), and surgical debridement remains the key element in the management of FG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, poor vascularization and antibiotic degradation limit antibiotic delivery to the fascial tissue (Montrief et al, 2019). In the face of these obstacles, it has been suggested that therapeutic plasma exchange can improve organ function and reduce mortality by decreasing circulating inflammatory mediators in the blood (Saifee et al, 2017). Unfortunately, this method is still not recommended as adjuvant therapy in the treatment of necrotizing soft tissue infections (Saifee et al, 2017), and surgical debridement remains the key element in the management of FG.…”
Section: Discussionmentioning
confidence: 99%
“…Saifee et al 56 suggested that therapeutic plasma exchange can decrease circulating inflammatory mediators in the blood and could improve organ function and reduce mortality. However, this method is still not recommended as adjuvant therapy in the treatment of necrotizing soft tissue infections.…”
Section: Plasma Exchangementioning
confidence: 99%
“…90,91 Further fluid administration should be guided by hemodynamic parameters (heart rate, blood pressure, urine output, and lactate clearance) to gauge responsiveness to initial fluid resuscitation. 89,[91][92][93][94] Vasopressors may be used to support In patients with salt or freshwater exposure, consider adding: Doxycycline…”
Section: Resuscitationmentioning
confidence: 99%
“…There is a theoretical benefit of neutralizing streptococcal toxins in NSTI associated with toxic shock syndrome; however, this has not been shown as of yet to be beneficial in the literature. 89,97 Therapeutic plasma exchange (TPE) has been considered and is thought to remove inflammatory mediators. 89 The current literature is not yet mature enough to make a recommendation at this time.…”
Section: Intravenous Immunoglobulins and Therapeutic Plasma Exchangementioning
confidence: 99%
See 1 more Smart Citation